Managerial control of voting rights - Stulz, RenéM. (Journal of Financial Economics, 1988)
This paper analyzes how managerial control of voting rights affects firm value and financing policies. It shows that an increase in the fraction of voting rights controlled by management decreases the probability of a successful tender offer and increases the premium offered if a tender offer is made. Depending on whether managerial control of voting rights is small or large, shareholders' wealth increases or falls when management strengthens its control of voting rights. Management can change the fraction of the votes it controls through capital structure changes, corporate charter amendments, and the acquisition of shareholder clienteles.